2022
DOI: 10.1002/acr.24515
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Association Between Disease Activity and Disability in Early Axial Spondyloarthritis: Results From a Prospective Observational Study of Inflammatory Back Pain

Abstract: Objective Our primary objective was to study the long‐term association between disease activity and disability in axial spondyloarthritis (SpA). Our secondary objective was to define patient profiles according to their level of disability. Methods We analyzed data collected during the first 5 years of follow‐up of a large early axial SpA cohort, the Devenir des Spondylarthropathies Indifferénciées Récentes (DESIR) cohort. Multivariable models were built to study the association between the Health Assessment Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Multivariate regression identified worse global functioning (ASAS-HI), impaired physical function (BASFI) and higher disease activity (BASDAI) as the main predictors of impaired WP. Other studies have already identified a correlation between these PROs and treatment,11 17 32–34 suggesting that treatments which target alleviating symptoms related to physical function and disease activity will likely also improve WP. BASDAI subvariables only reached significance in the univariate models, suggesting they were not able to explain any variance beyond the other predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate regression identified worse global functioning (ASAS-HI), impaired physical function (BASFI) and higher disease activity (BASDAI) as the main predictors of impaired WP. Other studies have already identified a correlation between these PROs and treatment,11 17 32–34 suggesting that treatments which target alleviating symptoms related to physical function and disease activity will likely also improve WP. BASDAI subvariables only reached significance in the univariate models, suggesting they were not able to explain any variance beyond the other predictors.…”
Section: Discussionmentioning
confidence: 99%
“…6 With the increased application of TA B L E 3 Gender, HLA-B27, and hip involvement comparison in patients with axSpA. In axSpA patients, DA is a critical factor affecting HRQoL, 4 with the ASDAS being an appropriate measure of DA. 21 Recent international recommendations emphasize the importance of measuring and controlling DA to achieve inflammation abrogation and improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This restriction results in reduced PA, while the ongoing pain and inflammation also limited PF by causing stiffness and restricting joint mobility. 4 Additionally, DA often coincides with fatigue, leading to decreased energy levels and reduced motivation for physical activities. 27 This fatigue impedes daily tasks and adherence to exercise routines, negatively impacting both PF and PA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Many other studies and a recent systematic literature review have confirmed a link between disease activity and HRQOL. 5,16,17 The magnitude of this link varies according to the statistical methods used and the population analyzed. One important point to consider when discussing the link between PROs and disease activity is that in axSpA, disease activity scores are deeply influenced by the patient's assessment of their symptoms.…”
mentioning
confidence: 99%